PELAKSANAAN EKSTRAKURIKULER DRUMBAND DI SMAN 3 SOLOK SELATAN KECAMATAN SANGIR - Fitrawati Fitrawati; Idawati Syarif; Yensharti Yensharti (FBS Universitas Negeri Padang, 2012)
This research aim to for the mendeskripsikan of extracurricular execution of Drumband in SMAN 3 Solok South District of Sangir. this Type Research is qualitative with descriptive method of analysis. Technique data collecting by book study, observation, interview, and documentation. Research Instrument is ownself constructively observation sheet perceiving activity of teacher/coach during activity take place. Technique analyse data by collecting primary data classification and of sekunder later;then process as according to device which have been made. Research finding that is performing a practice 1 times within a week every day Saturday, with select participant of class of X and of XI which have had ability play at Drumband during SMP. Keywords: implementation, extracurricular, drumband.